Mammographic Vascular Microcalcifications as a Surrogate Parameter for Coronary Heart Disease: Correlation to Cardiac Computer Tomography and Proposal of a Classification Score - Jonathan Andreas Saenger; Ela Uenal; Eugen Mann; Stephan Winnik; Urs Eriksson; Andreas Boss (Diagnostics)
Objective: This study develops a BI-RADS-like scoring system for vascular microcalcifications in mammographies, correlating breast arterial calcification (BAC) in a mammography with coronary artery calcification (CAC), and specifying differences between microcalcifications caused by BAC and microcalcifications potentially associated with malignant disease. Materials and Methods: This retrospective single-center cohort study evaluated 124 consecutive female patients (with a median age of 57 years). The presence of CAC was evaluated based on the Agatston score obtained from non-enhanced coronary computed tomography, and the calcifications detected in the mammography were graded on a four-point Likert scale, with the following criteria: (1) no visible or sporadically scattered microcalcifications, (2) suspicious microcalcification not distinguishable from breast arterial calcification, (3) minor breast artery calcifications, and (4) major breast artery calcifications. Inter-rater agreement was assessed in three readers using the Fleiss’ kappa, and the correlation between CAC and BAC was evaluated using the Spearman’s rank-order and by the calculation of sensitivity/specificity. Results: The reliability of the visual classification of BAC was high, with an overall Fleiss’ kappa for inter-rater agreement of 0.76 (ranging between 0.62 and 0.89 depending on the score). In 15.1% of patients, a BAC score of two was assigned indicating calcifications indistinguishable regarding vascular or malignant origin. In 17.7% of patients, minor or major breast artery calcifications were found (BAC 3–4). BAC was more prevalent among the patients with CAC (p < 0.001), and the severity of CAC increased with the BAC score; in the group with a BAC score of one, 15% of patients exhibited mild and severe CAC, in those with a BAC of two, this was 31%, in those with BAC of three, this was 38%, and in those with a BAC of four, this was 44%. The sensitivity for detecting CAC, based on the mammographic BAC score, was 30.3% at a specificity of 96.7%. Conclusions: The standardized visual grading of BAC in mammographies on a four-point scale is feasible with substantial interobserver agreement, potentially improving the treatment of patients with suspicious microcalcifications and CAC.